Characterization and adaptive compression of a multi-soliton laser source - Rasskazov, Gennady (Opt Express, 2017)
Ultrashort pulse generation in the 1600 nm wavelength region is required for deep-tissue biomedical imaging. We report on the characterization and adaptive compression of a multi-soliton output spanning >300 nm from a large-mode area photonic-crystal fiber rod for two separate laser setups. Sub-30 fs pulses are generated by first compressing of each soliton individually, and then followed by coherently combining all of the pulses in the train, which are separated by hundreds of femtoseconds. Simulations of the source, together with amplitude and phase coherence measurements are provided.